Analisis Pengaruh Struktur Kepemilikan Publik, Ukuran Perusahaan, Profitabilitas, Risiko Keuangan, Proporsi Dewan Komisaris dan Penerapan GCG Terhadap Praktik Perataan Laba pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2008-2010 - Dwi Astuti, Agustina Tunjung; Sudantoko, Djoko (PRESTASI, 2013)
In this study, researcher examined six factors that influence practice of smoothing earnings is the structure of public ownership, firm size, profitability, financial risk, the proportion of independent board and the application of good corporate governance by testing at the manufacturing companies listed on the Stock Exchange in 2008-2011. The purpose of this study was to analyze influence between the structure of public ownership, firm size, profitability, financial risk, the proportion of independent board and the application of good corporate governance on earnings smoothing practices in manufacturing companies on the Stock Exchange. The research sample of 34 manufacturing companies in the BEI, the method used is purposive sampling is a sampling method by specifying the criteria listed manufacturing companies on the Stock Exchange year period 2008-2010, the company successively experienced net profit in the post , manufacturing companies that reported complete data and the companies that implement good corporate governance in full, with the audit committee. The results obtained figures on the significance test of Hosmer and lameshow test 0.057> significance level (Î± = 5% = 0.05). It is said that the model is acceptable because it fits with the observation data. Logistic regression equation model in this study are: Y = 13996-7948 SKP - 0734 UK - 0.87 ROA - RK 2516 + 0045 + 0113 BOD GCG + e. The results obtained partial regression test results that the public ownership structure variables showed the significance of <0.05, and the other independent variables showed the results of> 0.05. This suggests that the only variables are public kepemikan structure significantly influence the practice of smoothing earnings, other independent variables had no significant effect.Keywords: Public Ownership Structure, Company Size, Profitability, Risk Finance, The proportion of the Board of Commissioners of the Independent, Implementation of Good Corporate Governance.